2003
DOI: 10.1097/01.blo.0000093887.12372.3d
|View full text |Cite
|
Sign up to set email alerts
|

Rotationplasty After Failed Limb-Sparing Tumor Surgery

Abstract: Rotationplasty was used in two cases of failed limb salvage in adults after tumor resection and reconstruction. Each patient had distal femoral osteosarcoma, one treated with osteoarticular allograft reconstruction, the other with a custom endoprosthetic reconstruction. Both patients had failure attributable to infection, and after multiple surgeries, elected to have rotationplasty. Both had complications associated with the rotationplasty but went on to have functional limbs with Musculoskeletal Tumor Society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Large humeral or femoral segments can be reconstructed with endoprosthesis of new prosthetic materials [17,18]. We performed more endoprosthesis (27%) than osteosynthesis (17%), as these are beneficial for selected patients with metastatic tumors and bone loss, what we and others have shown before [19-22]. A wide resection (R0) could, on the first sight, significantly improve survival (p = 0.0123) in comparison to R1 or R2 resection.…”
Section: Discussionmentioning
confidence: 98%
“…Large humeral or femoral segments can be reconstructed with endoprosthesis of new prosthetic materials [17,18]. We performed more endoprosthesis (27%) than osteosynthesis (17%), as these are beneficial for selected patients with metastatic tumors and bone loss, what we and others have shown before [19-22]. A wide resection (R0) could, on the first sight, significantly improve survival (p = 0.0123) in comparison to R1 or R2 resection.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have reported using rotationplasty as a successful treatment option for a failed limb salvage procedure, albeit with higher complication rates than primary rotationplasty [5,15]. The only patient in our cohort who did not have osteosarcoma underwent rotationplasty after failure of the primary resection for synovial sarcoma.…”
Section: Discussionmentioning
confidence: 75%
“…However, the patient should always be aware that a conversion in the setting of infection carries a significant risk of thigh amputation 7, 8. Rotationplasty should be considered in selected patients for whom an amputation is being considered after failed limb salvage surgery 21. Rotationplasty allows the patient to actively control the knee, which results in coordinated gait pattern, which is similar to the gait of the able‐bodied population, and better than in subjects with above‐knee amputation and also with knee arthrodesis 22–29.…”
Section: Discussionmentioning
confidence: 99%